Three Stages of Marriage - Victor William Harris (EDIS, 2012)
Most marriages go through at least three distinct stages: romantic love, disillusionment and distraction, and dissolution, adjustment with resignation, or adjustment with contentment. Researchers have found that couples utilize at least four general strategies for adjusting to the realities of long-term marriages with contentment. Learn more in this 3-page fact sheet written by Victor William Harris, and published by the UF Department of Family, Youth and Community Sciences, March 2012.